The Peter J. Braun Russian Mennonite Archive, 1803-1920 : a research guide - Epp, Ingrid I. (Ingrid Ilse) (Russian Mennonite studies., 1996)
The original documents that make up the Peter J. Braun Russian Mennonite Archive were assembled in the Molochna Mennonite settlement in southern Ukraine between 1917 and 1929. Named in honour of Peter J. Braun, a leading educator and the person most intimately involved in the establishment and development of the archive, it was created by Russian Mennonites to foster historical consciousness and research at a time when their community and land were being threatened by Russian extremist nationalists as part of a campaign against imperial Germany. Confiscated by Soviet authorities in 1929, the archive disappeared from public view for more than sixty years. It was rediscovered in 1990 in the state archives in Odessa; in 1990 and 1991, the entire archive was microfilmed and brought to Canada. The collection consists of more than 130,000 pages of documents, organized in some 3,000 chronologically arranged files. By far the most extensive collection of in-group Russian Mennonite sources surviving from the Imperial period, it spans a wide range of subjects concerning the largest and most influential Mennonite community in Russia. The archive provides fresh and concrete detail on the Russian Mennonite story, the development of the Black Sea Steppe frontier, and ethnic and religious minorities in southern Ukraine. The guide to this unique primary source material consists of a historical introduction, a detailed listing and description of the contents, a guide to the use of the microfilm (tables, keys, and a glossary), as well as illustrations and maps.